Influence of employees' sex, number of dependants and family responsibility on job involvement (2004)
Having a paid job constitute an important component of human needs. When on the job however, the level of job involvement differ among employees. Some salient personal characteristics of employees are seldom considered in discussing job involvement in Nigeria. This necessitated this study, which investigated the influence of sex, number of dependants, and family responsibility on job involvement. A total of 200 participants drawn from two multinational corporations in Ibadan, Nigeria took part in the study that adopted the exposit factor design. Questionnaires were used for data collection. Females were found to be more involved in their job than the male workers that participated in the study. Number of dependants was found to have high positive relationship with job involvement. It was concluded that there is no justification for the gender stereotype that encourage the deliberate exclusion of females from certain jobs in organisations. Having high number of dependants does not hinder job involvement. The need for gender sensitive policies was recommended for Management of organisaiions